Mycobacterium tuberculosis WhiB3 Responds to Vacuolar pH-induced Changes in Mycothiol Redox Potential to Modulate Phagosomal Maturation and Virulence - Mansi Mehta; Raju S. Rajmani; Amit Singh (2015)
The ability of Mycobacterium tuberculosis to resist intraphagosomal stresses, such as oxygen radicals and low pH, is critical for its persistence. Here, we show that a cytoplasmic redox sensor, WhiB3, and the major M. tuberculosis thiol, mycothiol (MSH), are required to resist acidic stress during infection. WhiB3 regulates the expression of genes involved in lipid anabolism, secretion, and redox metabolism, in response to acidic pH. Furthermore, inactivation of the MSH pathway subverted the expression of whiB3 along with other pH-specific genes in M. tuberculosis. Using a genetic biosensor of mycothiol redox potential (EMSH), we demonstrated that a modest decrease in phagosomal pH is sufficient to generate redox heterogeneity in EMSH of the M. tuberculosis population in a WhiB3-dependent manner. Data indicate that M. tuberculosis needs low pH as a signal to alter cytoplasmic EMSH, which activates WhiB3-mediated gene expression and acid resistance. Importantly, WhiB3 regulates intraphagosomal pH by down-regulating the expression of innate immune genes and blocking phagosomal maturation. We show that this block in phagosomal maturation is in part due to WhiB3-dependent production of polyketide lipids. Consistent with these observations, MtbΔwhiB3 displayed intramacrophage survival defect, which can be rescued bypharmacological inhibition of phagosomal acidification. Last, MtbΔwhiB3 displayed marked attenuation in the lungs of guinea pigs. Altogether, our study revealed an intimate link between vacuolar acidification, redox physiology, and virulence in M. tuberculosis and discovered WhiB3 as crucial mediator of phagosomal maturation arrest and acid resistance in M. tuberculosis.